Geographies of dissociation: Value creation, 'dark' places, and 'missing' links. Issue 1 (March 2019) - Ibert, Oliver; Hess, Martin; Kleibert, Jana; Müller, Felix; Power, Dominic
In this article, we seek to contribute to cultural-economic geography debates on the social construction of economic value. We widen the focus on already well-studied associations between branded commodities and other entities representing nonmonetary values by also considering what we refer to as 'dissociations'. Dissociation denotes practices of weakening or obscuring negative links between a branded commodity and other entities in order to let the desired associations overrule undesired ones. We highlight the strategic agency behind such dissociations and thus focus on actors' proactive relational work to prevent negative associations from becoming salient as well as their reactive practices of managing reputational crises. The article situates the study of dissociations in human geography and pays particular attention to the geographies of dissociation along territorial, relational, and topological lines.